Online, Distance Legal Education as an Agent of Social Change - Perlin, Michael L. (2011)
New York Law School (NYLS) created its online, distance learning mental disability law program in an effort to provide education in an area of the law that remains hidden in most law school curricula. Since 2000, it has offered its mental disability law courses in an online, distance learning format to its own students, to law students from other US-based law schools, to mental health professionals, to students in all the allied mental health professions and in the fields of criminology and criminal justice, and to activists and advocates (including members of the psychiatric survivor movement). It has offered the courses in partnership with other US-based law schools and has offered them in conjunction with universities in Nicaragua and Japan. In doing so, it has been able to work with advocates in other nations to pursue progressive social change in all aspects of mental disability law and social policy. The courses offered cover all aspects of mental disability law -- civil and criminal, public and private, domestic and criminal, skills and substantive -- and specifically consider the impact of race, gender, class and culture on this area of the law. This is a pivotal development in the history of American legal education, and it is essential that those committed to social change (especially in the context of the relationship between the methodologies of legaleducation and the substance of what is being taught) acknowledge that the standard model of providing legaleducation is, essentially, broken, and that it is mandatory that we look to new means for providing legaleducation -- in economic, efficient and interdisciplinary ways -- to our students in innovative ways that demonstrate the linkage between education and social change. This reconceptualization of the standard legaleducation model is especially timely in light of recent research demonstrating how the Internet has already become an important provider of advocacy services and advocacy information to many persons with disabilities, and how inaccessible most current websites are to many persons with disabilities. After using this model of instruction for over a decade -- now offering 13 courses and both a Masters degree and Advanced Certificate in mental disability law studies -- we believe that this pedagogical model offers a redemptive opportunity to reshape legal education in the new “transformative” era